RANCANG BANGUN E-COMMERCE BERBASIS WEB RESPONSIVE DAN MOBILE ANDROID PADA UMKM AIKORI NATURAL LEATHER BAG SEMARANG SEBAGAI MEDIA PROMOSI DAN INFORMASI - Putri Sekarudya Puspita Aruningtyas; Putut Haribowo; Jumi Jumi (JOBS (Jurnal Of Business Studies), 2019)
The development of the internet in Indonesia is one factor in improving the economy in Indonesia. UMKM Aikori Natural Leather Bag Semarang is a micro company engaged in the creative industry that produces handicraft items made from cow leather. Since its establishment in 2011, the company has only introduced its leather craft products offline. So many customers find it difficult to get information about the latest product collections from UMKM Aikori Natural Leather Bag Semarang. To overcome this problem a web was created using one of the CMS (Content Management System) namely Wordpress which can expand market share and also facilitate UMKM Aikori Natural Leather Bag Semarang in managing product sales. The purpose of this research is to build online-based sales media using Wordpress content management system so that it can expand market share that cannot be reached by the previous system. The method used in this research is the System Development Life Cycle, namely Waterfall, where there are several stages, namely requirements definition, system and software design, implementation and until testing, system testing, operation and maintenance. The results of this research show that a good web can contain the latest information so that it can be accessed by customers anytime and anywhere.